The Role of Value Co-Creation in ICT-based Service Innovation within Tourism Context - Brilliane, Citra Septi; Novani, Santi; Farhana, Adinda (Journal of Indonesian Tourism and Development Studies, 2021)
The rapid development of technology has shifted the conventional tourism industry towards the digitalization of the tourism sector. The emergence of travel booking platforms, as a form of technology-based service innovation, is able to simplify traveling activities and previous works of literature have indicated a positive relationship towards customer satisfaction. However, tourist's behavior has change become more demanding to involve in the creation of value in accordance with their needs and wants. The concept of value co-creation elaborates this issue, offering a new concept of value creation and new roles between service providers and tourists. This study aims to examine value co-creation as mediating variable between IT-based service innovation and customer satisfaction, using DART measurements and SEM-PLS is used to assess the model. The findings prove that IT-based service innovation positively influences value co-creation between users, which can increase customer satisfaction. However, IT-based service innovation does not have a direct impact on customer satisfaction, which indicates that value co-creation fully mediating the relationship between service innovation and customer satisfaction. Thus to enhance customer satisfaction, service providers need to propose service innovation that facilitates customer involvement in value creation, which can be supported by technology. Keywords: Customer satisfaction, Service innovation, Tourism, Travel booking platform, Value co-creation.